ANALISIS PERUMUSAN STRATEGI WAJIB BELAJAR 12 TAHUN DI KABUPATEN MAJALENGKA - Nurdin, Diding; Sugardha, Irza Adya; Mirfani, Aceng Muhtaram (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
In developing country, it takes quality human resources through education. The government needs to create a program that can make the distribution of education in Indonesia. This paper aimed at analyzing the existing compulsory education programs and factors that affect the realization of the 12 years compulsory education program in Majalengka by using SWOT analysis techniques. This paper used descriptive qualitative approach. The data were collected through interviews, documentation and observation. The result provided the strategy of the implementation 12 years compulsory education was raising awareness of the people of Majalengka about the importance of education especially the 12 years compulsory education.